Emerging clinical trends and perspectives on comorbid patterns of mental disorders in research - Fava, Giovanni A. (Int J Methods Psychiatr Res, 2013)
Comorbidity is a well‐established and documented phenomenon in mental disorders and medicine with heuristic value. The concept of comorbidity remains however poorly defined and lacks a comprehensive and coherent theoretical framework. There is a need to develop coherent methodological strategies in order to promote a fuller understanding of the implications of comorbidity and to exploit its potential value with regard to etiopathogenic and therapeutic issues. This position paper makes recommendations of improved methodological standards and procedures and discusses a range of options that can provide incremental information that is likely to improve therapeutic outcomes. Copyright © 2013 John Wiley & Sons, Ltd.